Analisis Kesalahan Penggunaan Kata Pelengkap Arah 趋向补语 (Qūxiàng Bǔyǔ) 来 (Lái) Dan 去 (Qù) Pada Kalimat Bahasa Mandarin Siswa Kelas Xi Mas An Nuriyah Bontocini Jeneponto - Sasmita Sasmita; Misnawaty Usman; Arini Junaeny (Universitas Negeri Makassar, 2022)
This research was conducted to obtain data and information regarding the analysis of complementary words of directions (Qūxiàng Bǔyǔ) 来 (Lái) and 去 (Qù) of Mandarin sentences in MAS An-Nuriyah Bontocini Jeneponto, grade XI. The type of this research used descriptive qualitative. The population in this study were 40 students of class XI MAS An-Nuriyah Bontocini Jeneponto consisting of 18 students of class XI science and 20 students of class XI social studies. The sample of this study was 18 students, and the sampling method was full sampling. The data of this study were obtained through an error analysis test of the complementary word of direction来 (Lái) and 去 (Qù) in Mandarin sentences of class XI Students of MAS An-Nuriyah Bontocini Jeneponto. The data analysis used percentage technique with the results of the percentage analysis that 28%, it shows that the analysis of errors in the direction of complementary words of direction来 (Lái) and 去 (Qù) in of Mandarin sentences in MAS An-Nuriyah Bontocini Jeneponto, grade XI .